(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
Industrial ecology is a concept that aims to design industrial systems in a manner that mimics natural ecosystems, minimizing waste generation and reducing environmental impact. This abstract provides an overview of the principles and strategies involved in the design of closed-loop systems within industrial ecology. In recent years, the negative impact of industrial processes on the environment has become a growing concern. Traditional linear production systems, characterized by a "take-make-dispose" approach, have resulted in significant waste generation and environmental degradation. To address this issue, the concept of a closed-loop system has gained prominence. A closed-loop system aims to minimize waste and reduce environmental impact by designing processes that maximize resource efficiency, recycle materials, and minimize the release of harmful substances. This research focuses on the design of a closed-loop system that incorporates principles of circular economy and sustainable manufacturing practices. The proposed system emphasizes the integration of various components, including material selection, product design, manufacturing processes, and end-of-life management. The primary objective is to develop a comprehensive framework that enables the transformation of linear production systems into circular systems, ensuring the efficient use of resources throughout the product life cycle. The methodology for designing the closed-loop system involves several steps. Firstly, a detailed analysis of the existing production processes and waste generation patterns is conducted to identify areas for improvement. Next, strategies for waste reduction and resource optimization are explored, such as the adoption of eco-design principles, implementation of recycling and reprocessing techniques, and establishment of reverse logistics systems.